Zástavní listiny Zikmunda Lucemburského na církevní statky (1420--1437) - Bárta, Stanislav (Spisy Masarykovy univerzity v Brně, Filozofická fakulta, 2016)
The book analyses Sigismund's of Luxembourg lien on ecclesiastical goods as an instrument of his financial policy in the Kingdom of Bohemia. At first, it presents available resources and historical literature on the subject. The main part of the book is an analysis of Sigismund's pledges on ecclesiastical goods in chronological order. This analysis is supplemented by a probe into the proportions of the Chotěšov and Zbraslav monasteries. An important part of the publication is also a catalogue of over 400 pledges and other similar acts and documents important for understanding the mechanism of pledges on ecclesiastical goods.